Analisis Kemampuan Komunikasi Matematis Ditinjau dari Tipe Kepribadian Guardian dan Idealist - Melya, Lekok; Supriadi, Nanang (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this study is to describe the mathematical communication skills of high school students in terms of guardian and idealist personality types. Subjects in this study were taken using a purposive random sampling technique of two students from class X senior high school in Bandar Lampung with different personality types, that is one student with guardian personality type and one student with a idealist personality type based on David Keirsey's personality dimensions, with personality type initial guardian (NAP) and initial idealist personality type (DBD). Mathematical communication skills are analyzed based on the following criteria : (1) the ability to write down what is known and asked about the questions; (2) the ability to write answers according to the purpose of the questions; (3) the ability to write down reasons for answering questions; (4) the ability to make mathematical terms and symbols; (5) the ability to make images that are relevant to the questions; (6) the ability to make conclusions in their own language. The results showed that subjects with guardian personality type were only able to master the five criteria of mathematical communication ability. The subject was unable to conclude with his own language. The results showed that subjects with idealist personality type were only able to master the five criteria of mathematical communication ability but the subject does not master the third criterian, the subject is unable to write down the reasons for answering the question.